Analysis of Pharmaceutical Care Services in Hospital Pharmacy Installation in Jambi City - Andy Brata; Lailan Azizah (Poltekkes Kemenkes Jambi, 2018)
Abstract Background: The care of pharmacy or Pharmaceutical care is a form of optimizing the role performed by pharmacists on patients in conducting medical therapy so that they can improve the patient's health status. Pharmacists play a role in providing consultation, information and education (IEC) related to the treatment therapies that patients undergo, directing patients to adopt healthy lifestyles so that the treatment success can be achieved, and monitoring the results of treatment therapies that have been carried out by patients and collaborating with other health professions which of course aim to improve the quality of life of patients. The purpose of the study was to determine the implementation of pharmacist practices in hospitals in Jambi City and pharmacist awareness of the implementation of pharmacy care in hospitals in Jambi City Method: The sample was determined by 55 pharmacists, who were selected by exhause sampling. Conclusion: The results of the study showed that simultaneously both dimensions of pharmaceutical services had a significant effect on the implementation of pharmaceutical care; while partially one variable (pharmacist awareness about pharmacy care) has a significant influence (p <0.05), while the current pharmacist practice variable in the hospital does not have a significant effect. Pharmacy care services in hospital pharmacy installations in Jambi city are not influenced by current pharmaceutical practices in hospitals. Where pharmacists consider awareness of pharmacy care services while in practice not. So that the implementation of pharmacy care is influenced by the pharmacist's awareness of the care of pharmacy.